An ERP study on how subsequent sentence context can influence previous world knowledge constraints. (February 2015) - Xu, Guiping; Zhong, Weifang; Jin, Hua; Mo, Lei
Abstract: In an ERP study, following stimuli with a world knowledge violation we added a sentence-level context which made a world knowledge violation more acceptable in order to investigate how participants processed the subsequent sentence context. Sentences consisting of five Chinese words were of three experimental types: correct sentences with correct world knowledge and coherent sentence meaning, incoherent sentences with a world knowledge violation and incoherent sentence meaning, and 're-coherent' sentences with a world knowledge violation but coherent sentence meaning. The results showed both incoherent and re-coherent conditions modulated N400, elicited by the critical word which contained the world knowledge violation, and a negative deflection elicited by the final word, in a similar way, reflecting the immediate world knowledge integration of critical word and low predictability of final word respectively. An additional negative deflection was elicited only by the final word in the incoherent condition, probably reflecting global sentence context integration. These results provide support for immediate world knowledge integration, and indicate that subsequent new sentence context can immediately influence previous world knowledge constraints. Highlights: An ERP study on how sentence context can influence world knowledge constraints. To examine whether subsequent context could overrule previous violation constraint. World knowledge violations were immediately integrated in the middle of sentence. Subsequent context immediately overruled previous world knowledge constraints. Study complements previous studies on world knowledge and sentence comprehension.